Prognostyczne własności wybranych wskaźników finansowych - Appenzeller, Dorota (Predictive Properties of the Selected Financial Ratios, 2006)
The hypothesis verified and empirically confirmed in the presented study was, that the trends of financial ratios for sound companies differ significantly from trends of the same financial ratios for distressed companies, when their bankruptcy approaches. The empirical analysis was based on the financial information for 95 publicly traded Polish companies (37 distressed and 58 sound companies). 21 financial ratios were tested in order to verify their predictive abilities. The obtained results are in detail described in the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 28-38